Controllable Synthesis of 3D Hollow‐Carbon‐Spheres/Graphene‐Flake Hybrid Nanostructures from Polymer Nanocomposite by Self‐Assembly and Feasibility for Lithium‐Ion Batteries. (13th August 2015) - Li, Qianqian; Yao, Kun; Zhang, Guangchun; Gong, Jiang; Mijowska, Ewa; Kierzek, Krzysztof; Chen, Xuecheng; Zhao, Xi; Tang, Tao
Abstract : 3D hollow‐carbon‐spheres/graphene‐flake hybrid nanostructures are controllably prepared from a polypropylene/montmorillonite/Fe3 O4 composite by a self‐assembly and subsequent carbonization process. More importantly, in the resultant hollow‐carbon‐spheres/graphene‐flake hybrid structures, the monodispersed small hollow carbon spheres can be distributed on the graphene flake with controllable density. The obtained hollow‐carbon‐spheres/graphene‐flake hybrid nanostructures show improved performance in lithium‐ion batteries.